FROM GREEN RECRUITMENT TO HIGH PERFORMANCE: A MEDIATED MODEL OF SUSTAINABLE HRM IN ECOTOURISM DESTINATIONS - Muhammad Faisal; Irsan Tricahyadinata; Wirasmi Wardhani (RADJA PUBLIKA, 2025)
The growing emphasis on environmental sustainability in the tourism sector has accelerated the adoption of Green Human Resource Management (GHRM) practices. This study investigates the effect of green recruitment and development on employee performance, with job satisfaction as a mediating variable, within the context of ecotourism destinations in East Kalimantan, Indonesia. The primary objective is to examine how environmentally oriented HR strategies contribute to improving employee outcomes in sustainable tourism settings. A quantitative approach was employed using Structural Equation Modeling (SEM) to analyze data collected from 355 employees through structured surveys. The results revealed that both green recruitment and green development significantly influence employee performance, both directly and indirectly, through enhanced job satisfaction. Notably, green development exerted the strongest influence on job satisfaction, affirming its role in building a committed and high-performing workforce. These findings offer theoretical contributions to the development of GHRM frameworks by validating job satisfaction as a key psychological pathway. Practically, this study highlights the importance of embedding sustainability values in HR practices to strengthen organizational performance in nature-based tourism enterprises.